Changing Medical Education, Overnight: The Curricular Response to COVID-19 of Nine Medical Schools. Issue 3 (27th May 2021) - Binks, Andrew P.; LeClair, Renée J.; Willey, Joanne M.; Brenner, Judith M.; Pickering, James D.; Moore, Jesse S.; Huggett, Kathryn N.; Everling, Kathleen M.; Arnott, John A.; Croniger, Colleen M.; Zehle, Christa H.; Kranea, N. Kevin; et al.
Abstract: Issue: Calls to change medical education have been frequent, persistent, and generally limited to alterations in content or structural re-organization. Self-imposed barriers have prevented adoption of more radical pedagogical approaches, so recent predictions of the 'inevitability' of medical education transitioning to online delivery seemed unlikely. Then in March 2020 the COVID-19 pandemic forced medical schools to overcome established barriers overnight and make the most rapid curricular shift in medical education's history. We share the collated reports of nine medical schools and postulate how recent responses may influence future medical education. Evidence: While extraneous pandemic-related factors make it impossible to scientifically distinguish the impact of the curricular changes, some themes emerged. The rapid transition to online delivery was made possible by all schools having learning management systems and key electronic resources already blended into their curricula; we were closer to online delivery than anticipated. Student engagement with online delivery varied with different pedagogies used and the importance of social learning and interaction along with autonomy in learning were apparent. These are factors known to enhance online learning, and the student-centered modalities (e.g. problem-based learning) that included them appeared to be more engaging. Assumptions that the new online environment would be easily adopted and embraced by 'technophilic' students did not always hold true. Achieving true distance medical education will take longer than this 'overnight' response, but adhering to best practices for online education may open a new realm of possibilities. Implications: While this experience did not confirm that online medical education is really 'inevitable, ' it revealed that it is possible . Thoughtfully blending more online components into a medical curriculum will allow us to take advantage of this environment's strengths such as efficiency and the ability to support asynchronous and autonomous learning that engage and foster intrinsic learning in our students. While maintaining aspects of social interaction, online learning could enhance pre-clinical medical education by allowing integration and collaboration among classes of medical students, other health professionals, and even between medical schools. What remains to be seen is whether COVID-19 provided the experience, vision and courage for medical education to change, or whether the old barriers will rise again when the pandemic is over.